2017
DOI: 10.2196/mhealth.7336
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App for the Self-Management of Type 1 Diabetes Among Adolescents: A Randomized Controlled Trial

Abstract: BackgroundWhile optimal blood glucose control is known to reduce the long-term complications associated with type 1 diabetes mellitus, adolescents often struggle to achieve their blood glucose targets. However, their strong propensity toward technology presents a unique opportunity for the delivery of novel self-management interventions. To support type 1 diabetes self-management in this population, we developed the diabetes self-management app bant, which included wireless blood glucose reading transfer, out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(187 citation statements)
references
References 40 publications
(47 reference statements)
5
179
0
3
Order By: Relevance
“…Similar to our results, the three studies found no improvement in HbA1c compared to the control group. However, one study [34] found a statistically significant association between increased self-monitored blood glucose and improved HbA1c. Unfortunately, comparability is limited by the small number of existing studies and differences in intervention design.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to our results, the three studies found no improvement in HbA1c compared to the control group. However, one study [34] found a statistically significant association between increased self-monitored blood glucose and improved HbA1c. Unfortunately, comparability is limited by the small number of existing studies and differences in intervention design.…”
Section: Discussionmentioning
confidence: 96%
“…Berndt et al [33] tested an application to collect data and provide clinical support in a four-week RCT (n=68; ages 8-18). Finally, Goyal et al [34] tested an mHealth application in a 12-month RCT (n=92; ages 12-15). The application facilitated feedback on the transfer of blood glucose readings from a glucometer, rewarding action.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the site with the highest app usage site spent the greatest time and resources on implementation. It is increasingly evident that digital health apps designed to improve chronic disease self-management require ongoing patient engagement with the app as a key determinant of clinical impact [28][29][30][31][32]. Therefore, a successful implementation and evaluation of these apps requires careful consideration of factors that impact patient app utilization [32].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of downloading the app, participants were given the intervention on a second phone they used for the duration of the study in an attempt to standardize implementation by the funder. However, the use of a second phone to deliver e-health interventions has been a noted barrier to usage in previous studies and future mobile app evaluations would likely benefit from allowing participants to utilize their own smart phones when possible [30]. Given previous evidence on the benefits of strong PCP participation in diabetes self-management apps, the use of DEPs as the primary site of recruitment likely had a negative impact on enrollment, usage and clinical impact [41,42].…”
Section: Limitationsmentioning
confidence: 99%
“…Researchers must assess the efficacy of medical strategies rather than focusing on patients' failures to adhere to recommendations of questionable therapeutic value [4]. Effective healthcare management may not only prevent chronic disease complications but also reduce overall disease cost and family burden and improve patients' quality of life [1,[5][6][7].…”
Section: Information Technology Transformationmentioning
confidence: 99%